Antioxidant activity of thyme waste extract in O/W emulsions - EL-GEUNDOUZ, Soukaina (2019)
Thymus vulgaris (thyme) is an aromatic plant and its essential oil has been applied as antimicrobial and antioxidant due to the presence of phenolic compounds. However, after steam distillation, the deodorized plant material is rejected, despite the possible presence of bioactive compounds. Ethanolic thyme waste extract revealed the presence of benzoic acid, 4-hydroxybenzoic acid, ferulic acid, caffeic acid, and sinapic acid. This waste thyme extract had the capacity for preventing the formation of primary and secondary lipid oxidation products in emulsions O/W (oil in water), constituted by diverse proportions of wheat and almond oils, without interfering with the viscosity parameters, for 10 weeks, at 37 °C. The increasing proportion of almond oil (≥50%) in the emulsion increases its resistance to oxidation, which is improved with the presence of an optimal concentration of tested thyme waste extract (0.02% and 0.04%). The waste thyme extract can, therefore, be used as an antioxidant either in food or pharmaceutical emulsions O/W, replacing the synthetic antioxidants.